"Bundle" Practices and Ventilator-Associated Events: Not Enough. (19th September 2016) - O'Horo, John C.; Lan, Haitao; Thongprayoon, Charat; Schenck, Louis; Ahmed, Adil; Dziadzko, Mikhail
Abstract : OBJECTIVE: Ventilator-associated events (VAEs) are nosocomial events correlated with length of stay, costs, and mortality. Current ventilator bundle practices target the older definition of ventilator-associated pneumonia and have not been systematically evaluated for their impact on VAEs. DESIGN: Retrospective cohort study. SETTING: Tertiary medical center between January 2012 and August 2014. PARTICIPANTS: All adult patients ventilated for at least 24 hours at our institution. INTERVENTIONS: We conducted univariate analyses for compliance with each element; we focused on VAEs occurring within a 2-day window of failure to meet any ventilator bundle element. We used Cox proportional hazard models to assess the effect of stress ulcer prophylaxis, deep vein thrombosis (DVT) prophylaxis, oral care, and sedation breaks on VAEs. We adjusted models for gender, age, and Acute Physiology and Chronic Health Evaluation (APACHE) III scores. RESULTS: Our cohort comprised 2, 660 patients with 16, 858 ventilator days and 77 VAEs. Adjusting for APACHE score and gender, only oral care was associated with a reduction in the risk of VAE (hazard ratio [HR], 0.44; 95% confidence interval [CI], 0.26–0.77). The DVT prophylaxis and sedation breaks did not show any significant impact on VAEs. Stress ulcer prophylaxis trended toward an increased risk of VAE (HR, 1.59; 95% CI, 1.00–2.56). CONCLUSION: Although limited by a low baseline rate of VAEs, existing ventilator bundle practices do not appear to target VAEs well. Oral care is clearly important, but the impact of DVT prophylaxis, sedation breaks, and especially stress ulcer prophylaxis are questionable at best. Infect Control Hosp Epidemiol 2016;1453–1457